Seasonally Evolving Trends Explain the North‐South Dipole Pattern Observed in Tibetan Plateau Precipitation - Ma, Jieru; Ren, Hong‐Li; Cai, Ming; Huang, Jianping (Geophysical research letters, 2023)
The Tibetan Plateau (TP) precipitation is experiencing the north‐south dipole tendency pattern since 1979. In this study, we identify four primary seasonally evolving patterns (SEPs) that explain approximately 50% of the total variance in precipitation variability over the TP. These SEPs contribute 60%–90% of the spatial mean amplitude of precipitation trends across seasons. In particular, the second SEP that features a north‐south dipole pattern dominates the annual mean trend of the precipitation over the TP. The interdecadal variability of the seasonally evolving north‐south dipole pattern is linked to the interdecadal variations of summer Silk Road Pattern and Indian monsoon. These findings suggest that the climate variability expressed through SEPs could potentially serve as a significant source for the interdecadal rainfall prediction. Plain Language Summary The Tibetan Plateau (TP) is experiencing the north‐wetting‐south‐drying trend due to the imbalance of the Asian water tower since 1979, influencing the water supply to billions of people and regional and global climate. However, the characteristics of the seasonally evolving variations of precipitation across seasons on multiyear timescales, as well as the associated major circulation patterns, remain unknown. Here we identify four primary seasonally evolving patterns (SEPs) and focus on investigating their corresponding long‐term trends and interdecadal variations. These four modes collectively contribute by 60%–90% of the spatial mean amplitude of precipitation trends across seasons. In particular, the trend of the second SEP that features a north‐south dipole explains the spatio‐temporal disparity of the total precipitation trend, displaying the strongest amplitude in summer over the TP. Our findings provide insight into the climate variability manifested in SEPs as a major source for the interdecadal prediction of rainfall evolution in the Asian water tower. Key Points Seasonally evolving patterns (SEPs) explain 60%–90% of the spatial mean amplitude of total precipitation trend over the Tibetan Plateau The second SEP trend with a north‐south dipole pattern mainly contributes to the spatio‐temporal disparity of the total precipitation trend The seasonally evolving north‐south dipole trend is linked to the Silk Road pattern and the Indian monsoon variations